[PP.34.39]: INCREASED PULSE PRESSURE AS PREDICTOR OF EARLY ISCHEMIC STROKE OUTCOMES. (June 2015) - Alonzo>, C.>; Brescacin, L.; Zurru, M.; Fucile, G.; Pigretti, S.; Camera, L.; Cristiano, E.; Waisman, G.
Abstract : Objective: Vascular stiffening of large arteries leads to wider pulse pressure (PP), and has been related to increased risk of clinical events and worse outcomes. We aim to evaluate the relationship between early stroke outcomes and 30-day PP. Design and method: Acute ischemic stroke patients were prospectively included in PROTEGE-ACV, a multidisciplinary secondary stroke prevention program. Demographic data and pre-stroke vascular risk factor (VRF) profile and control were obtained from electronic medical records. For the purpose of the analysis, stroke outcomes (cognition by MMSE and clock-drawing test –CDT– and functional status by Barthel index and m-Rankin) were analyzed according to 30-day PP quintiles. Results: 1215 ischemic stroke patients (mean age 75 ± 10 years, 55% females) were included between December 2006 and December 2013. Patients in the higher quintiles of PP were older (p 0.001) and more likely to be women (p 0.001), had higher prevalence of dyslipidemia (p 0.0001), diabetes (p 0.0001), atrial fibrillation (p 0.001), chronic kidney disease (p 0.001), coronary heart disease (p 0.00001) and peripheral arteriopathy (p 0.0001). They also had worse pre-stroke VRF control despite more intensive pharmacological treatment. Stroke outcomes are shown in the table. Figure. No caption available. Conclusions: In our cohort wide pulse pressure was related with post-stroke disability and cognitive impairment. This hemodynamic variable should be considered by practitioners, along with other traditional risk factors, in treatment strategies after stroke.